Resonances 1990
DOI: 10.1142/9789814540223_0039
|View full text |Cite
|
Sign up to set email alerts
|

Relaxation Effects in Nuclear Magnetic Resonance Absorption

Abstract: The exchange of energy between a system of nuclear spins immersed in a strong magnetic field, and the heat reservoir consisting of the other degrees of freedom (the "lattice") of the substance containing the magnetic nuclei, serves to bring the spin system into equilibrium at a finite temperature. In this condition the system can absorb energy from an applied radiofrequency field. With the absorption of energy, however, the spin temperature tends to rise and the rate of absorption to decrease. Through this "sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
445
2
10

Year Published

2000
2000
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 319 publications
(479 citation statements)
references
References 0 publications
22
445
2
10
Order By: Relevance
“…At this autoxidation phase, polymerization/oligomerization products are known to be formed (Choe and Min, ). It is well reported that when analyzing large molecules such as polymers and or oligomers in a magnetic field, the T 1 relaxation time is stable and/or increases and T 2 declines (Bloembergen et al, ). This pattern is seen in the case of rapeseed oil and will be further discussed for PUFA oils.…”
Section: Resultsmentioning
confidence: 99%
“…At this autoxidation phase, polymerization/oligomerization products are known to be formed (Choe and Min, ). It is well reported that when analyzing large molecules such as polymers and or oligomers in a magnetic field, the T 1 relaxation time is stable and/or increases and T 2 declines (Bloembergen et al, ). This pattern is seen in the case of rapeseed oil and will be further discussed for PUFA oils.…”
Section: Resultsmentioning
confidence: 99%
“…Figure 7 shows R2=T2­1 plotted as a function of dispersed Fe concentration for the FePt@SiO 2 (Rubpy) and Fe 2 O 3 @SiO 2 (Rubpy) nanoparticles. The T 2 relaxivity, r 2 , indicates how strongly the paramagnet influences the proton spin relaxation of the surrounding water and is determined from the concentration dependence of R 2 [66,67,69]:…”
Section: Resultsmentioning
confidence: 99%
“…The average difference in precontrast T 1 between 1.5T and 3T was larger for myocardium (0.16 ± 0.06 sec) than blood (0.08 ± 0.13 sec). The fact that myocardium T 1 increased more than blood from 1.5T to 3T may be attributed to the greater free water content and shorter molecular correlation times in blood (36), which would cause less field dependence on T 1 , in much the same way that water and CSF T 1 appear almost insensitive to field change. The trend toward similar blood and myocardium T 1 values at high field strength may lower image contrast between blood and myocardium on T 1 ‐weighted images.…”
Section: Discussionmentioning
confidence: 99%